The Effect of Animal Protein MP-ASI & Visual Education on Stunted Children's Waist Circumference - Warsini, Warsini; Aminingsih, Sri; Kristanto, Budi; Khairunisa, Fatimatuzzahra; Barros, Carmelita (Adi Husada Nursing Journal, 2025)
Adequate nutrition is very important for the body, especially during the growth and development of children. Stunting is a condition of impaired growth in children under five years of age due to chronic malnutrition. This study aims to determine the effect of providing additional animal protein through complementary feeding (MP-ASI) and education based on visual media on the anthropometric parameter of waist circumference in children with stunting. This study used a quasi-experimental method with a pre-test and post-test design. The study involved a sample of 9 respondents who were children with stunting in the working area of the Jayengan Public Health Center, Surakarta City. The sample criteria included children with a waist circumference not appropriate for their age. Total sampling was used as the sampling technique, meaning all eligible individuals from the population were included in the study. The implications of this research indicate that the combination of providing additional animal protein through complementary feeding (MP-ASI) and visual media-based education is an effective strategy for improving the nutritional status of children with stunting. Specifically, this combined intervention significantly increased the children's waist circumference after the program. This demonstrates that the method successfully improved a crucial anthropometric parameter related to the nutritional status of stunted children. The practical implication is that this approach can be implemented by health workers in public health centers (puskesmas) or community health posts (posyandu) as a nutritional program model to accelerate stunting reduction, particularly in areas with high stunting prevalence and limited access to information.